Analysis of Nitrogen, Phosporus and Potassium Concentration in Liquid Organic Fertlizers of vegetable Waste, Charcoal and Snails - Anin Nafis, Fika Fatwa; Kustono, Djoko; Hapsari, Anindya (citeus, 2023)
Nitrogen, phosphorus and potassium concentration in liquid organic fertilizer can be obtained from organic materials. Liquid organic fertilizer can be made from vegetable waste, charcoal, and gold snail (Pomacea canaliculata L.). This study aimed to know the concentration of nitrogen, phosphorus and potassium in liquid organic fertilizers of waste vegetable, charcoal and snail. Methods used to test nitrogen was the Kjeldahl method, while potassium and phosphorus tested with spectrophotometer. The results showed that the concentration of nitrogen, phosphorus and potassium in liquid organic fertilizers of waste vegetable, charcoal and snail were 0,2612 percent; 0,0334 percent; and 0,1421 percent. This concentration didn’t meet the standard of liquid organic fertilizers quality based on MOA No. 70 of 2010 which is 3 until 6 percent.